The Use of Gliphosate Herbicides on Growth, Yield and Residue of Corn - Muhammad Danang Faqihhudin, Haryadi, dan Heni Purnamawati (Faculty of Agriculture, Universitas Gadjah Mada jointly with PISPI, 2014)
The objective of the research was to determine the effect of glyphosate herbicides on growth and yield of corn. This experiments was conducted at Sindang Barang Farm, Bogor from April to August 2013. This experiment used a Randomized Block Design with one factor namely dose of active ingredient glyphosate herbicide. The experiment consisted of 5 treatments such as control, and herbicide with doses 3, 4, 5, and 6 l ha-1. Plot size was 4 x 4 m, with plant spacing of 70 x 20 cm. Plots were treated on week before planting. Growth and yield of corn were influenced by herbicide treatments. Herbicide treatment at doses of 4 l ha-1 to produce seed growth, number of leaves, plant height, and leaf area the highest compared with other treatments. Similiar results also occur in the yield parameters of corn. Increased herbicide doses above 4 l ha-1 lower the better outcomes observed that variable growth and yield of corn. Based on glyphosate residue analysis indicated that each treatments contained residues of glyphosate. Herbicide treatment doses of 6 l ha-1 showed the highest residual value compared with other treatments. Based on glyphosate residue analysis in this research is still below the minimum limits of residue.